Migration as Security Issue - New Challenges and Risks of States - Zendelovski, Goran; Cvetkovski, Sergej (Faculty of Philosophy – Skopje, 2018)
The phenomenon of migration is as old as human history. The reasons for migration were numerous. Some of them were voluntary and others were forced. As in the past, today it is intensively approaching the explanation of migration, with some glorifying it, and others marginalizing it. Migration processes are continually linked to current contemporary social, political, economic, social, cultural and security developments. In certain countries and regions, the question arises as to whether migration brings them development, stagnation, stability or insecurity? The effects of international migration can be interpreted in many ways. On the one hand, the dynamics of the economic processes of globalization have increased mobility of people, capital and services that have enabled people to improve their economic status, to gain a higher level of education and better health care services. On the other hand, there are assurances that migration is one of the global issues that led to fundamental changes and the creation of new structures and a different development of international relations in the world. The migration processes have increased the risks and threats to national and regional security. Trinity migration, security and globalization are closely linked to the emergence of conflicts, hunger, poverty, climate change, economic crises and political repression. In particular, current migration movements with religious and fundamentalist content were trigger for deterioration the security situation in foreign countries. Due to the security implications of migration, the perception of security in many countries has changed, and political nationalist movements have been formed, whose views have been directed to protecting from the waves of migrants.
Keywords: Migration, Security implications, Risks, States.